Non-coding RNA Regulated Cross-Talk Between Mitochondria and Other Cellular Compartments - Huang, Jinliang; Wu, Sipeng; Wang, Pengcheng; Wang, Geng (Frontiers in Cell and Developmental Biology, 2021)
Mitochondria are the main hubs for cellular energy production. Metabolites produced in mitochondria not only feed many important biosynthesis pathways but also function as signaling molecules. Mitochondrial biosynthesis requires collaboration of both nuclear and mitochondrial gene expression systems. In addition, mitochondria have to quickly respond to changes inside and outside the cells and have their own functional states reported to the nucleus and other cellular compartments. The underlying molecular mechanisms of these complex regulations have not been well understood. Recent evidence indicates that in addition to small molecules, non-coding RNAs may contribute to the communication between mitochondria and other cellular compartments and may even serve as signals. In this review, we summarize the current knowledge about mitochondrial non-coding RNAs (including nucleus-encoded non-coding RNAs that are imported into mitochondria and mitochondrion-encoded non-coding RNAs that are exported), their trafficking and their functions in co-regulation of mitochondrial and other cellular processes.